Desire for information and alternative therapies of pet owners is associated with empathy and partnership‐building of veterinarians. (31st March 2021) - Merle, R.; Küper, A.
Abstract : Objectives: The relationship between the pet owners' desire for information and preference of alternative therapies and the veterinarians' ability to build partnership and communicate empathically was investigated using quantitative multifactorial analysis. Materials and Methods: In an online survey, 1270 German pet owners were asked about their experience of veterinary appointments regarding communication and relationship building. Additional questions included the type and number of pets, years of animal husbandry, age, gender and education level. The factors associated with the pet owners' desire for further information and alternative therapies were analysed in two multivariable linear models. A recently published structural equation model consolidated the following as latent factors: veterinarian's empathic communication, veterinarian's partnership building, pet owners' desire for further information and pet owners' desire for alternative therapies ( e.g. non‐veterinary practitioners). Results: The two veterinarian‐related factors of empathic communication and partnership building were positively associated with each other, but negatively associated with the pet owners' desires . Dog owners and participants who owned animals for more than 2 years expressed less desire for further information . The desire for further information decreased with increasing age. The desire for alternative therapies was more among animal owners of more than 2 years and those visiting the same veterinary practice for over 2 years. Clinical Significance: Veterinarians' empathic communication and partnership building are key factors that satisfy clients' desires for information and alternative therapies. This comprises communicational skills regarding information sharing, as well as emotional aspects.